Harmonic scalpel impact on blood loss and operating time in major head and neck surgery: a randomized clinical trial. Issue 1 (December 2016) - Fritz, Dieter; Matthews, T.; Chandarana, Shamir; Nakoneshny, Steven; Dort, Joseph
Abstract Background Long operating time and high blood loss contribute to post-surgical morbidity. Therefore, strategies to reduce these factors should to be tested using robust methods. The purpose of this study was to evaluate the impact of using the harmonic scalpel on operating time and blood loss in patients undergoing resection for advanced oral cancer (OSCC). Methods Thirty-six adult head and neck cancer patients with advanced OSCC requiring primary tumor resection with uni- or bi- lateral selective neck dissection from July 2012 to September 2014 were randomized to either the control group (traditional surgery) or the experimental group (harmonic surgery). Patients older than 18 years who were able to provide informed consent were eligible. Primary outcomes of interest were: intraoperative blood loss (mL) and operative time (minutes) for the ablative part of the surgery. Results Mean blood loss in the experimental group was 260 mL versus 403 mL in the control group (p = 0.08). Mean operative time was 140 min in the experimental group and 159 min in the control group (p = 0.2). Conclusions In this randomized controlled trial, use of the harmonic scalpel did not effect intraoperative blood loss or OR time in patients undergoing surgery for advanced OSCC. Trial registration ClinicalTrials.gov, NCT02017834 .